PERTUMBUHAN TANAMAN GAHARU (Aquilaria sp.) DI DESA GIRI AGUNG KECAMATAN SEBULU KABUPATEN KUTAI KARTANEGARA PROVINSI KALIMANTAN TIMUR - Datu Bandar Pramana; Jumani Jumani; Heni Emawati (Universitas 17 Agustus 1945 Samarinda, 2013)
The experiment was conducted at the Community Forestry area in the Giri Agung Village of Sebulu Sub District, Kutai Regency. Planting implementation was in 2006. Research carried out for about 2 effective months (from May to June 2012). The object was Gaharu crop of 6 years old in the Giri Agung Village with the total samples 30 crops planted at the top of hill, and 30 crops planted at the slope. The data was analysed with SPSS 12 t-test to determine the differences in growth at the top and on the slopes at the significant level 95%. The results showed that the Gaharu crop growth at top and at slope hill were not significantly different on both crop diameter and height growth by the t test. The results of the statistical test using t-test showed that t-count is less than t-table which means there is no significant difference in the average of crop height at the top and slope. There were several limiting factors for optimum growth of Gaharu. They were soil factors, especially pH and limitation availability of some macro and micro nutrients, because almost all the nutrients required by the Gaharu is generally lacking. Therefore, it needed an improvement or increase in the availability of nutrients by fertilizing with both organic and inorganic fertilizers that are required by the Gaharu.